Multi-Omics Joint Analysis of Molecular Mechanisms of Compound Essential Oils Inhibiting Spoilage Yeast in Paocai - Xinyi Wu; Zhiyan Zhu; Hao Tian; Li Liu; Xuerui Li; Jun Pan; Yifan Hu; Zhirui Niu; Hanmo Wang; Xiuwei Liu (Foods)
Pichia manshurica is the main spoilage fungus that causes the deterioration of paocai. Our previous study found that the compound essential oils (CEOs) of lemon, lemongrass, and nutmeg had a good inhibitory effect; however, the antimicrobial mechanism was unknown. In order to elucidate the mechanism of action of the CEO in inhibiting P. manshurica, transcriptomics and metabolomics were used for joint analysis. The results showed that the minimum inhibitory concentration (MIC) of P. manshurica was 2 µL/mL, and the combined multi omics analyses indicated that the treatment of the CEO disrupted the ABC transporters, glycophospholipid metabolism, and nucleotide metabolism of P. manshurica, leading to the disruption of the integrity of P. manshurica cell wall and cell membrane, resulting in energy and metabolic dysfunction, and ultimately achieving the effect of inhibiting P. manshurica. The results of this study provided new insights into the mechanism of P. manshurica inhibition by CEOs, and provide a reference basis for the development of food-related bacteriostatic agents by CEOs.